Time-integrated and time-resolved optical studies of InGaN quantum dots - Robinson, J; James Robinson (2005)
The construction of a high-resolution optical microscope system for micro-photoluminescence (µ-PL) spectroscopy is described, and a range of time-integrated and time-resolved experimental work on single InGaN quantum dots (QDs) is presented. Time-integrated measurements demonstrate the existence of InGaN QDs in three different samples via the presence of sharp exciton recombination lines in the µ-PL spectra. The narrowest peaks display a linewidth Γ of ~230 µeV, implying a decoherence time T2 ≥5.7 ps. Time-resolved measurements on exciton recombination lines from single self-assembled InGaN QDs reveal typical lifetimes of ~2.0 ns (which decrease with increasing temperature), while typical lifetimes for excitons in single selectively-grown micropyramidal InGaN QDs are found to be ~0.4 ns. The shorter exciton recombination lifetime in selectively-grown QDs is believed to be due to a stronger coupling of these QDs to the underlying quantum well. Temporal fluctuations (on a timescale of seconds) in the energy, intensity and FWHM of µ-PL peaks arising from the recombination of excitons in single self-assembled InGaN QDs are observed. These are attributed to transient Stark shifts induced by a fluctuating local charge distribution as carriers become trapped in defect states in the vicinity of the QDs. Time-integrated power-dependent measurements are used to demonstrate the presence of biexciton states in single self-assembled InGaN QDs. The exciton–biexciton energy splitting is found to be ~41 meV, in agreement with values predicted by theoretical calculations. Time-resolved studies of the biexciton and exciton decay curves reveal a coupling as the exciton population is refilled by biexciton decays. The biexciton lifetime is found to be ~1.4 ns, compared to an exciton lifetime of ~1.0 ns. Lateral electric fields are applied to a single self-assembled InGaN QD using aluminium electrodes lithographically defined on the sample surface. Application of fields of the order of ~0.17 MVcm-1 is found to cause both a red-shift and a reduction in the intensity of the exciton recombination peak in the µ-PL spectrum.